The Strategies used by English Teachers in Teaching Speaking at MTs Nurul Falah Air Mesu Timur - Rahmawati, Rizki (EEdJ: English Education Journal, 2024)
This study aims to find out the kinds of the strategies used by English teachers in teaching speaking. From these statement, the researcher analyzed the strategies used by English teacher in teaching speaking at Mts Nurul Falah. The objectives of this research were: to elaborate the strategies used by English teacher in teaching speaking at MTs Nurul Falah Air Mesu Timur and to elaborate the implementation in teaching speaking at MTs Nurul Falah Air Mesu Timur. The researcher used descriptive qualitative method and data collection was based on observation and interview. Miles and Huberman technique of analyzing data was used by having data reduction, data display, and drawing conclusion. The researcher collected data was used to observe the process of how the strategies used by English teacher in teaching speaking in class, the interview was used to support the results of the observation checklist. Therefore, this research used triangulation technique method. The findings of this research showed that the teachers applied many strategies to teaching speaking in the classroom, which are roleplay, drilling, discussion, picture describing, storytelling, brainstorming, and creative tasks.